(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
This writing discusses the issue of Malay language (Bahasa Melayu) before the Second World War by focusing on Lembaga Malaya. As a newspaper that spread many views and ideas about Bahasa Melayu, Lembaga Melaya was responsible in calling on the local community to restore the dignity of their own language after the introduction of foreign languages by colonizers eroded the position of Bahasa Melayu as the main language. The development of Bahasa Melayu before British colonization is provided early in the discussion before comprehensively discussing Lembaga Melaya’s struggle in reviving the language. This writing used descriptive analysis method on Lembaga Melaya, supported by other primary and secondary sources. Several statistical data on the said topic were also included. The discussion of the topic’s scope and time only covers incidences and progress from the 20th century until before the start of the Second World War. This period saw the significant development of the writing and publishing of newspapers and magazines among the local community in Johor. Equipped with its own objectives and focus on the state of Johor as the birthplace of Lembaga Melaya, this article contains the policies and strategies planned by the British to erode the position of Bahasa Melayu in Malaya. This article also describes the cries and calls to defend the dignity of Bahasa Melayu in Johor, and examines Lembaga Melaya’s struggle in issues related to Bahasa Melayu. This writing also provides an overview of Lembaga Melaya’s role in defending and dignifying Bahasa Melayu until results were seen. Full text: PDF